2023
DOI: 10.3390/healthcare11202714
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, Attitudes and Willingness to Donate Biological Samples to a Biobank: A Survey of a Representative Sample of Polish Citizens

Łukasz Pronicki,
Marcin Czech,
Mariusz Gujski
et al.

Abstract: Biotechnology is developing at an ever-increasing pace, and the progressive computerization of health care and research is making it increasingly easy to share data. One of the fastest growing areas is biobanking. However, even with the best equipment and the best trained staff, a biobank will be useless without donors. For this reason, we have decided to gauge Polish citizens’ awareness and attitudes towards biobanking and their willingness to donate biological samples. For this purpose the survey was conduct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 41 publications
(86 reference statements)
0
4
0
Order By: Relevance
“…Also recent study conducted among adult Poles showed that the biobank awareness among adult Polish citizens is low, as only 20.9% were familiar with the idea of biobanking. However, 65.3% declared the willingness to share their biospecimens and annotated data for biobank research (Pronicki et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also recent study conducted among adult Poles showed that the biobank awareness among adult Polish citizens is low, as only 20.9% were familiar with the idea of biobanking. However, 65.3% declared the willingness to share their biospecimens and annotated data for biobank research (Pronicki et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Although there are several studies on the attitudes of Polish citizens towards biobanking of human biological material (HBM) for research purposes (Majchrowska et al, 2022;Pawlikowski et al, 2022;Domaradzki et al, 2023;Pronicki et al, 2023), there remains a shortage of studies on the attitudes of (future) pharmacists on research biobanks. Thus, this study was designed to assess knowledge and attitudes of Polish pharmacy students on research biobanks.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have revealed scant biobank awareness among the Polish population [ 49 – 54 ] so the questionnaire began with the short definition of research biobanks and all the questions used simple descriptive language without technical terminology. All questions were designed as close-ended items offering respondents a limited set of pre-defined and simple answers to choose from.…”
Section: Methodsmentioning
confidence: 99%
“…However, although the research on the people’s views on biobank research is growing rapidly, over the last decade only 25 research on cancer patients’ perspective have been conducted, according to the PubMed database [ 28 , 32 48 ]. Similarly, while there are only a few studies assessing the views of the Poles on the attitudes towards biobanking and donation of HBM they focus on the general population [ 49 – 54 ], but there remains a shortage of research on the perception of biobank research among Polish cancer patients. This study therefore seeks to explore oncology patients’ views on the donation of biospecimens for research purposes, including: (1) awareness regarding biobank research, (2) willingness to donate (cancer) tissue remaining after medical procedure for research purposes, (3) motivation for (non)participation, (4) type of tissues they would be willing to donate for research purposes, and (5) factors associated with patients decisions to donate tissue for biobank research.…”
Section: Introductionmentioning
confidence: 99%
“…This is of particular importance in countries like Poland where biobanking is still in the early development. In fact, although previous studies conducted in Poland demonstrated that there is high level of support for biobanking among the public, and many people declare the will to share their biospecimens for biobank research, it was also shown that biobanks rise some ethical and legal concerns [ 55 59 ]. One of the reasons for this is that although since 2016 the Polish Biobanking Network, gathering more than 50 biobanks, was established and operates within the European Biobanking and BioMolecular resources Research Infrastructure (BBMRI)-European Research Infrastructure Consortium (ERIC) [ 60 , 61 ], and the Quality Standards for Polish Biobanks (QSPB) which follow the Taipei Declaration, the Organisation for Economic Cooperation and Development (OECD) recommendations, the guidelines created by the International Society for Biological and Environmental Repositories (ISBER) and the International Organization for Standardization (ISO) established the general requirements for biobanking (9001: 2015, ISO 20387: 2018) [ 62 , 63 ], still in Poland there are no specific legal regulations regarding biobanking and rules for using human biological material and clinical data for scientific purposes [ 64 ].…”
Section: Introductionmentioning
confidence: 99%